Advances and prospects in the biosynthesis of vitamin B6 and its bioengineering as a cofactor of other chemicals. Issue 2 (3rd August 2022) - Wu, Lijuan; Liu, Linxia; Jin, Zhaoxia; Zhang, Dawei
Abstract: Vitamin B6 is an essential nutrient, which is widely used in food products, feed additives, pharmaceuticals, disease diagnosis, and other fields. Pyridoxal‐5′‐phosphate (PLP), the active form of vitamin B6, is an important coenzyme participating in a variety of enzyme reactions. At present, the oxazole method is mainly used for the production of vitamin B6, but toxic and corrosive intermediates produced in the synthesis process, which does not conform to the green manufacturing. Therefore, there is considerable interest in shifting from chemical processes to sustainable fermentation techniques and research on PLP metabolism of other valuable compounds. In this review, we will briefly describe the enzymes that PLP participated and focus on the advances in vitamin B6 biosynthesis and discuss its application to engineering bacteria that overproduce other commercially valuable substances including cadaverine, 3, 4‐dihydroxyphenylacetate‐l ‐alanine, γ‐aminobutyric acid, and l ‐phosphinothricin. It will provide a reference for the biosynthesis of vitamin B6 or other valuable compounds in which PLP participates in the reaction, and we also look forward to the future development prospect of PLP. Abstract : Vitamin B6 biosynthesis represents the future trend of green manufacturing. PLP is the coenzyme form of vitamin B6 and participates in a variety of metabolic enzymatic reactions. PLP bioengineering for the synthesis of other commercially valuable substances such as cadaverine, L‐DOPA, γ‐aminobutyric acid, and L‐phosphinothricin that rely on PLP‐dependent enzymes can potentially reduce the cost and the difficulty of isolation.